36-Year-Old Female with Catastrophic Antiphospholipid Syndrome Treated with Eculizumab: A Case Report and Review of Literature - Marianna Strakhan; Mariana Hurtado-Sbordoni; Nahun Galeas; Kamila Bakirhan; Karenza Alexis; Tarek Elrafei (Case Reports in Hematology)
Catastrophic antiphospholipid syndrome (CAPS) is a rare but potentially life-threatening condition characterized by diffuse vascular thrombosis, leading to multiple organ failure developing over a short period of time in the presence of positive antiphospholipid antibodies (aPL). CAPS is a severe form of antiphospholipid syndrome, developing in about 1% of cases of classic antiphospholipid syndrome, manifesting as microangiopathy, affecting small vessels of multiple organs. It is acute in onset, with majority of cases developing thrombocytopenia and less frequently hemolytic anemia and disseminated intravascular coagulation. Lupus anticoagulant and anticardiolipin antibodies have been reported as predominant antibodies associated with CAPS. Treatment options often utilized in CAPS include anticoagulation, steroids, plasma exchange, cyclophosphamide therapy, and intravenous immunoglobulin therapy. Even though the reported incidence of this condition is considered to be low, the mortality rate is approaching 50%. The high rate of mortality should warrant greater awareness among clinicians for timely diagnosis and treatment of this life-threatening condition. Studies have shown that complement activation plays a key role in the pathogenesis of aPL mediated thrombosis in CAPS. We report a case of a 36-year-old female admitted with clinical and laboratory findings consistent with CAPS successfully treated with eculizumab, a terminal complement inhibitor.